Moving higher education beyond Covid-19 : innovative and technology-enhanced approaches to teaching and learning - Visvizi, Anna, 1976-; Lytras, Miltiadis D., 1973-; Jamal Al-Lail, Haifa (Emerald studies in higher education, innovation and technology, 2023)
The Covid-19 pandemic caused mass disruption to higher education institutions (HEIs) across the world and has since led to vast debate on how to manage HEIs and how to deliver course content to students beyond the crisis. The emergency shift to remote learning has led many HEIs to adopt more flexible course delivery in the longer term. Drawing on international and multidisciplinary perspectives, Moving Higher Education Beyond Covid-19 explores how HEIs may use crises as an opportunity to develop, to transform, and to improve their institutional resilience. Authors draw on many novel and innovative practices mastered during the pandemic, including approaches to teaching, and the related learning and managerial practices. Collectively, the authors argue that Covid-19 has served as one of the most important push factors for universities to redesign their approaches to teaching and learning, and thereby also rethink their business models. With insights for researchers, course designers, and higher education leaders, Moving Higher Education Beyond Covid-19 is a must-read for moving your institution forward beyond the pandemic.